Konsep Bela Negara dalam Perspektif Islam dan Kristen Protestan - Sir, Tomi Azis Khan; Wanto, Sugeng; Siregar, Husna Sari (Lembaga Yasin AlSys, 2023)
The background of this research is that the authors are interested in conducting further research related to the Concept of State Defense in an Islamic and Christian Perspective because they want to know more about the concepts of the Koran and the Bible regarding state defense and how Islam and Christianity respond to state defense. Therefore, the author conducted a study entitled: